2011
DOI: 10.1534/genetics.111.127795
|View full text |Cite
|
Sign up to set email alerts
|

The Putzig-NURF Nucleosome Remodeling Complex Is Required for Ecdysone Receptor Signaling and Innate Immunity in Drosophila melanogaster

Abstract: Putzig (Pzg) was originally identified as being an integral component of the TRF2/DREF complex in Drosophila melanogaster, thereby regulating the transcriptional activation of replication-related genes. In a DREF-independent manner, Pzg was shown to mediate Notch target gene activation. This function of Pzg entails an association with the nucleosome remodeling factor complex NURF, which directly binds the ecdysone receptor EcR and coregulates targets of the EcR via the NURF-specific subunit Nurf-301. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Disruption of the components in PTTH and EcR signaling pathways can cause abnormal development in insects (Gu et al, 2011;Kugler et al, 2011), but it is still unknown how these are correlated with each other at the molecular level. In the present study, we performed a comprehensive screening of genes induced by 20E using DNA microarray …”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the components in PTTH and EcR signaling pathways can cause abnormal development in insects (Gu et al, 2011;Kugler et al, 2011), but it is still unknown how these are correlated with each other at the molecular level. In the present study, we performed a comprehensive screening of genes induced by 20E using DNA microarray …”
Section: Discussionmentioning
confidence: 99%
“…More recent work has revealed that Putzig (Pzg), a component of the TRF2/DREF replication complex, acts in concert with Nurf301 and Ken to repress JAK/STAT target genes (Fig. 3B and (Kugler et al, 2011)). In support of this model, loss of one copy of Nurf301 , ken or pzg singly or in combination significantly increases the hop Tum-l tumor incidence (Kwon et al, 2008; Kugler et al, 2011).…”
Section: The Jak/stat Pathway As a Major Driver Of Hematopoietic Tumorsmentioning
confidence: 99%
“…The chromatin-decondensing function of H3S10 phosphorylation, driven by Jil-1, is one possible mechanism for open chromatin formation, as described above. The Z4/Ptz subunit of the Chriz complex has also been suggested to cooperate with the nucleosome-remodeling factor complex NURF (Kugler et al, 2011) to support open chromatin formation. The whole region is depleted for inactive chromatin marks, like H3K9 and H3K27 trimethylation, and enriched for histone modifications typically found in active chromatin, like histone acetylation and H3K4 trimethylation.…”
Section: Discussionmentioning
confidence: 99%